PEMBERIAN KONSESI DALAM PEMBANGUNAN IBU KOTA NEGARA - Pratama, Aditya; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The capital city of Indonesia which is in DKI Jakarta Province will soon shift to East Kalimantan Province, which means it will also cause many changes not only in the economic cycle but also in the government system. The government center which has been based in DKI Jakarta will be moved to East Kalimantan. One of the government's plans in its vision to move IKN is for the Golden Indonesia Vision 2045. However, moving the National Capital actually gave rise to new problems regarding granting concessions to business actors in the National Capital Region over a period of almost 200 years (2 centuries). That have possibility for previously existing regulations to overlap with the practices that will be carried out, considering that the development of the National Capital is a sustainable development that is included in the National Strategic Project.Keywords: The Capital Nations, Consesssion, Government.